Home oxygen for children with neurodisability—do we know why we are using it?. (29th September 2015) - Martin, K; Hollingsworth, S; Crawford, C; Williams, J; Marder, E; Wolff, A
Abstract : Aims: To review the use and monitoring of home oxygen in children with disability for palliative and non-palliative care purposes. Method: The caseload of a team of community nurses serving children with severe disability was reviewed to establish numbers and details of children on home oxygen. The monitoring arrangements according to community nurses were compared with parents' perception of monitoring and parameters ascertained by phone call. Results: The caseload was 77 children with neurodisability aged 3 months–18.5 years. 15 children (eight females) with age range 15 months–17 years (mean 8 years) had been receiving home oxygen in the past 12 months. Two children had neurodegenerative conditions, 13 had severe static neurodisability. Five children were receiving oxygen for symptomatic relief as part of palliative care: four continuously and one intermittently. Three other children were receiving continuous oxygen: one for chronic neonatal lung disease and two for upper airway problems causing recurrent cyanotic episodes. Seven others were receiving intermittent oxygen: five for treatment of hypoxia during recurrent acute lower respiratory tract infections, one for respiratory depression associated with seizures and one for potential emergencies occurring during school transport. All nursing records described the oxygen treatment in detail with appropriate monitoring arrangements. However, in four cases (25%) the indications for oxygen and the monitoring actually being used were very different according to parents. Conclusions: There were several discrepancies between the reasons for home oxygen and the target oxygen saturations according to community nurses' notes and parents' understanding. Monitoring arrangements were appropriate. No children had satisfactory written care plans and it was not recorded whether potential hazards of home oxygen had been discussed. Oxygen is a prescription treatment with some significant safety implications. Indications for its use in the palliative or non-palliative setting should be clear. Following this audit a communication sheet was devised, including indications for oxygen therapy, monitoring arrangements, information and support given.